Luteolin induces apoptosis in Philadelphia chromosome-positive acute lymphoblastic leukemia cell by regulating the PI3K/AKT signaling pathway - Ren, Qin; Li, Xiaobing; Ye, Xiangmei; Feng, Leiguang (Frontiers in Pharmacology, 2025)
IntroductionPhiladelphia chromosome-positive acute lymphoblastic leukemia (Ph + ALL) represents the most prevalent genetic subtype of adult acute lymphoblastic leukemia (ALL). Despite the availability of targeted therapy regimens, patients with comorbidities and older patients have poor prognoses. They are prone to relapse, necessitating the urgent identification of new safe and effective treatment options. Luteolin (LUT), a natural flavonoid compound, has demonstrated significant anticancer activity. However, its mechanism of action in the context of Ph + ALL remains poorly understood. The objective of this study was to elucidate the potential mechanisms underlying the action of luteolin in Ph + ALL.MethodsLuteolin-related targets and Ph + ALL associated targets were collected from several public databases. The intersection of these targets was then analyzed for protein-protein interactions (PPI). Additionally, we performed functional and pathway enrichment analyses employing the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) methodologies. Core targets were selected from the PPI network, and some of these targets were further verified through cellular experiments.ResultsA total of 568 luteolin targets and 1,063 Ph + ALL targets were identified, with 154 overlapping targets. The top ten targets with the highest degree values were selected as core targets, which include TP53, AKT1, ALB, TNF, JUN, IL6, EGFR, STAT3, CASP3, and BCL2. Based on GO and KEGG enrichment results, the phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) signaling pathway was further investigated. Cell experiments demonstrated that luteolin reduced the viability of SUP-B15 cells in a time- and concentration-dependent manner. Additionally, luteolin led to an increase in reactive oxygen species (ROS) accumulation, a decrease in mitochondrial membrane potential (MMP), and a reduction in ATP content in SUP-B15 cells. At the molecular level, luteolin significantly downregulated the protein expression of p-PI3K, p-AKT, p-STAT3 and BCL-2, while upregulating the protein expression of BAX, cleaved caspase-3, and cleaved caspase-9.ConclusionLuteolin may exert anti-Ph + ALL effects through the PI3K/AKT signaling pathway, accompanied by the regulation of other targets such as STAT3, which provides a theoretical basis for the development and screening of novel anti-Ph + ALL therapies.